How can AI help to enhance diversity and inclusion? - SIAU, Keng (Institutional Knowledge at Singapore Management University, 2019)
In many organizations, promoting diversity and enhancing inclusion are still major concerns. Unconscious biases and stereotyping cause us to have preconceived ideas about what an ideal employee or leader should look like. Unconscious biases are also a major roadblock to an inclusive environment and business culture. Organizations have been investing heavily in training programs for their employees attempting to changes these patterns. Human habits, especially unconscious ones, are not easy to overcome. This research looks at the use of AI to enhance diversity and inclusion in organizations. Literature has shown that a more diverse and inclusive workforce has a competitive advantage over those that do not. McKinsey & Company found that gender-diverse organizations are 15% more likely to outperform their peers and ethnically-diverse organizations are 34% more likely to do better than their peers. A PwC study of 36 countries that are part of the Organization for Economic Co-operation and Development (OECD) shows that enhancing the employment rate of older workers could add $2.6 trillion to the GDP of these nations. The advancement in AI and machine learning can play a role in creating unbiased mechanisms, processes, and tools to assist human decision making. For example, an AI-enabled recruitment system may assist in selecting job candidates to reduce individual biases and machine learning can influence talent decisions in HR. On the flip side, AI systems are created by humans and most AI systems use a massive amount of data in learning. The data used in machine learning may contain human biases. Organizations need to recognize these issues and overcome these problems. We need to be able to trust the AI systems to provide unbiased recommendations and solutions (Siau and Wang, 2018). This qualitative study will examine how organizations are using AI to enhance diversity and inclusion. In the first phase of the study, senior executives and diversity officers in various organizations will be interviewed. In the second phase of the research, the findings from the first phase will be used to design questionnaires and the survey will be administered in some organizations. Recruiting, employing, and retaining a diverse workforce, and enabling the diverse workforce to be fully involved and empowered are keys for a successful organization. It is unlikely that AI will eliminate the need for human input and intervention, at least not in the short term, (Siau, 2018; Wang and Siau, 2019) but AI can be a tool that can help to enhance diversity and inclusion in organizations. As a pioneering research in this area, this research will provide both academics and practitioners a deeper understanding of the use and impact of AI and machine learning in promoting diversity and inclusion in organizations.